The role of the international community in the South African transition: a critical review - Dormehl, Andries Christian (Rhodes University, Faculty of Humanities, Department of Political Studies, 1993)
There is a dearth of position papers on international participation in the South African transition. Political parties and organisations in South Africa instead spend most of their time describing various forms of desirous IC intervention after the transition. This might explain why most articles and academic papers on 'the role of the international community' are suffixed - in the 'new South Africa' or 'post-apartheid South Africa' - few focus on the actual transition and then mostly from a systemic perspective, broadly outlining the constraints imposed by the 'new world order'. Perhaps the first serious attempt to address this gap in the debate over South Africa's future was D. Kempton and L. Mosia's 'The International Community in South Africa's Transition to non-racial Democracy' (1992). Before multiparty negotiations collapsed in June 1992, Kempton and Mosia examined the attitudes toward international intervention of most of the CODESA participants, as well as the major actors that had remained outside CODESA. This paper takes up the issue where Kempton and Mosia left off. It tries to explain transitional politics since the IC introduced an on-the-ground presence after the UN Security Council debates on South Africa in July 1992. It asks why, eight months after multiparty talks were suspended, the IC has been unable to revive multiparty negotiations, has apparently had little or no impact on the violence, and despite events like Boipatong and Bisho, still plays a minor peacekeeping role, confined to observer status. The research describes internal and external components of international intervention, examines the rationale behind the agreed forms of international participation, and assesses the viability of the internationally-supported conflict-resolution and transition-management structures that were formed to facilitate the transition. The evidence uncovered by the research leads the author to the conclusion that more of an international role is necessary, and sooner rather than later, but he concedes that this is not feasible, or likely, under the status quo.
Keywords: Democracy -- South Africa|South Africa -- Politics and government -- 1989-1994|South Africa -- Foreign relations -- 1989-1994